2006
DOI: 10.1038/sj.bjc.6603414
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mitomycin C is catalysed by human recombinant NRH:quinone oxidoreductase 2 using reduced nicotinamide adenine dinucleotide as an electron donating co-factor

Abstract: NRH:Quinone Oxidoreductase 2 (NQO2) has been described as having no enzymatic activity with nicotinamide adenine dinucleotide (NADH) or NADPH as electron donating cosubstrates. Mitomycin C (MMC) is both a substrate for and a mechanistic inhibitor of the NQO2 homologue NQO1. NRH:quinone oxidoreductase 2 catalysed the reduction of MMC at pH 5.8 with NADH as a co-factor. This reaction results in species that inhibit the NQO2-mediated metabolism of CB1954. In addition, MMC caused an increase in DNA cross-links in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…This enzyme has been shown to be important for the prodrug activation of mitomycin C [38,39], an anticancer antibiotic used for treatment of bladder cancer and other tumours, and for product activation of the synthetic anticancer agent CB1954 that is currently in clinical trials [40]. QR2 is capable of metabolically activating various quinones and other compounds, via either 2- or 4-electron reductions, which can ultimately lead to cytotoxicity and cell death [38,41].…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme has been shown to be important for the prodrug activation of mitomycin C [38,39], an anticancer antibiotic used for treatment of bladder cancer and other tumours, and for product activation of the synthetic anticancer agent CB1954 that is currently in clinical trials [40]. QR2 is capable of metabolically activating various quinones and other compounds, via either 2- or 4-electron reductions, which can ultimately lead to cytotoxicity and cell death [38,41].…”
Section: Resultsmentioning
confidence: 99%
“…Belcourt et al (13) and Seow et al (14) also used clonogenic assays to assess cytotoxicity and it may be that this assay selects for cells with altered sensitivity to the drug. Selected clones may express other enzymes reported to activate MMC such as DT-diaphorase (17, 35), NRH:quinone oxidoreductase 2 (37, 38), NADPH-ferrodoxin reductase (39) or cytochrome b5 reductase (9); they may also express antioxidants that detoxify and protect against ROS-induced damage. In this regard, antioxidant enzymes including glutathione peroxidase, superoxide dismutase and catalase have all been shown to reduce or abolish MMC cytotoxicity in tumor cells in vitro (29, 40).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our findings that hypoxia has no effect on MMC-induced cytotoxicity. Other enzymes in CHO-OR cells that can mediate the two electron reduction of MMC include NRH:quinone oxidoreductase (37, 38). We also cannot exclude the possibility that other enzymes mediating the one electron reduction of MMC including NADH-cytochrome b5 reductase, xanthine oxidase and nitric oxide synthase also mediate cytotoxicity in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that either the MDA468 cells have sufficient NRH to catalyze turnover of NQO2 or alternatively, that other pyridine nucleotides in the cell can serve as a co-factor for NQO2. Interestingly, recent work showed that NQO2 can catalyze the reduction of mitomycin C using NADH as co-factor (Jamieson et al, 2006). The respective efficiencies of NQO1 and NQO2 at bioactivation of RH1 require further study.…”
Section: Discussionmentioning
confidence: 99%